Pengaruh Edukasi Media Booklet terhadap Pengetahuan Ibu tentang Pemilihan Kontrasepsi Pada Ibu Nifas di RSUD Muara Teweh: Penelitian - Yustika Kinasih; Novalia Widiya Ningrum; Frani Mariana; Putri Yuliantie (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The government continues to strive to suppress the population growth rate, one of which is through family planning programs. At Muara Teweh Regional Hospital, the coverage of postpartum family planning services from December 2024 to January 2025, out of 155 postpartum mothers, recorded 2 using IUDs and 17 using MOW. This study aims to determine the effect of booklet media education on postpartum mothers' knowledge about contraceptive selection. The design used was a Quasi Experimental Design with one group pre-test post-test on 15 postpartum mothers on days 1–3. The Shapiro-Wilk normality test showed that the data was not normal (p = 0.000), so the analysis was continued with the Wilcoxon test. The results, before education, 11 people (73.3%) had low knowledge and 4 people (26.7%) had high knowledge, while after education, only 2 people (13.3%) had low knowledge and 13 people (86.7%) had high knowledge. The Wilcoxon test showed p = 0.03 < 0.05, so that booklet education had a significant effect on increasing postpartum mothers' knowledge regarding contraceptive selection.